2021
DOI: 10.24140/2021/eb-978-989-757-154-1
|View full text |Cite
|
Sign up to set email alerts
|

C3Places - Using ICT for Co-Creation of Inclusive Public Places

Abstract: This e-book and correspondent platform MyC3Place present the collection of the outcomes carried out by the partners of the C3Places Project.It explores the new dynamics of open spaces as a trusted service for community and expands our understanding on how mediated public open spaces function, paying attention to stakeholders, local context and different social groups. The e-book shows how it's possible to increase the quality of public open spaces (squares, parks, green spaces) as a community’s service, reflec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
(23 reference statements)
0
0
0
Order By: Relevance
“…We observed that even if ICTs are used, government institutions have exclusionary practices for data collected by local residents and key stakeholders, mostly due to the lack of opportunities and the provision of institutional spaces to discuss topics related to PDMPS. We also encountered challenges comparable to those reported in the European context, specifically that human and technical resources are still required and that the requirements for time invested are too high for planners and decision-makers to benefit from using ICTs [8,24]. Without the institutional embedding of participatory processes, using the 'newest' ICTs will be useless, and the voice of local residents will remain ineffective for decision-making processes.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…We observed that even if ICTs are used, government institutions have exclusionary practices for data collected by local residents and key stakeholders, mostly due to the lack of opportunities and the provision of institutional spaces to discuss topics related to PDMPS. We also encountered challenges comparable to those reported in the European context, specifically that human and technical resources are still required and that the requirements for time invested are too high for planners and decision-makers to benefit from using ICTs [8,24]. Without the institutional embedding of participatory processes, using the 'newest' ICTs will be useless, and the voice of local residents will remain ineffective for decision-making processes.…”
Section: Discussionmentioning
confidence: 85%
“…Another approach involves operationalising different areas of knowledge and technologies to allow local residents to participate meaningfully in planning, designing or maintaining public spaces [3][4][5]. As long as they are not used as isolated solutions, digital platforms can become supportive tools that could enhance communication and interaction among residents and decision-makers to manage public spaces [8,24].…”
Section: The Role Of Icts In Supporting Social Participation In Plann...mentioning
confidence: 99%